The effect of grain size on viscoelastic relaxation behavior of Au thin films. (October 2018) - Mongkolsuttirat, Kittisun; Smyth, Jeffrey R.; Brown, Walter L.; Vinci, Richard P.
Abstract: The effect of grain size on viscoelastic relaxation behavior of Au thin films was investigated by using gas pressure bulge testing to measure the changing normalized plane-strain modulus as a function of time. We observed more rapid and extensive relaxation with increasing grain sizes. The normalized modulus of the Au films is shown to be linearly dependent on the square of the in-plane grain size. Transmission electron microscopy suggests that an increase in grain size allows a higher fraction of mobile dislocation segments to bow under an applied stress, resulting in a proportional increase of the relaxation of coarser-grained films. Graphical abstract: Unlabelled Image